Registration of acute viral hepatitis – an “Iceberg phenomenon” - Talalayev, K. A.; Kozishkurt, E. V. (Journal of Education, Health and Sport, 2018)
The quality of registration of acute liver damage caused by hepatitis A, B and C viruses can be questioned. A comparative study of the frequency of detection of serological markers of acute liver damages associated with three pathogens and indicators of officially registered morbidity was carried out. It has been established that in some cases the diagnosis of hepatitis A is established only on the basis of clinical symptoms and the exclusion of markers of acute damage by other hepatitis viruses. The results of serological studies on the detection of aHBcor IgM in patients with hepatitis symptoms suggest that in half of cases there is an under-registration of acute hepatitis B. The estimated incidence of acute hepatitis C, according to the identified markers (aHCV IgM), is more than 10 times higher than the recorded level. It is necessary to optimize the information subsystem of epidemiological surveillance of this group of diseases by organizing a vertical line between the diagnostic and therapeutic link in the health care system.